Manual de funciones para la Empresa COMUNICA-TE S.A. en la ciudad de Daule - Franco Morán, Kevin Vicente (2024)
This study focuses on proposing a functions manual to define and improve the functions performed by each collaborator in the company COMUNICA-TE S.A. For this, a descriptive research was developed with a mixed approach and research instruments such as the survey and interview aimed at workers and managers of the company. The need for a well-structured manual to optimize coordination, reduce conflicts and increase productivity was evident, due to problems in the management of functions that affected the fulfillment of specific objectives and operational efficiency. The proposal clearly defines the responsibilities and expectations of each position in alignment with the company's strategic objectives, facilitating better coordination and greater transparency in the assigned tasks. In addition, it is complemented with performance management tools to monitor and evaluate the effectiveness of the manual.............